Heat Stroke in the Era of Global Warming: A Call for Urgent Action - Ayesha Khan; Manahil Mubeen (Annals of Global Health)
Heat stroke (HS) represents a life-endangering condition that is due to an imbalance between heat generation and dissipation, owing to exposure to hot environments or strenuous exercise. HS is a medical condition that is gaining increased prevalence throughout the world due to a steady rise in temperature, and massive mortalities have been recorded among vulnerable populations. In 2024, extreme heat waves led to increased cases of HS and related fatalities globally, particularly in Karachi, Pakistan. This article reviews the pathophysiology, effects, treatment, and preventive strategies of HS management. Effective management includes prompt on-site cooling and symptomatic treatment followed by intensive care for severe cases. In keeping heat-related illnesses low, indoor stay, hydration, and public awareness campaigns play important roles. The urge of the article, therefore, is that HS demands very serious attention from the global arena and its proactive measures should be enforced to avert this medical emergency globally.